Financial Crisis, Confidence in Financial Markets and Participation in Private Pension Plans in Germany - Brandt, Ulrich; Zanker, Dagmar; Frommert, Dina (Socialinė teorija, empirija, politika ir praktika, 2024)
The financial crisis of 2008/2009 has not only left its mark on the value of retirement savings, but also on savings and investment behaviour. It has led to a loss of confidence in financial markets and its main protagonists. However, trust is a key mechanism for savings and investment decisions. We illustrate the loss of trust by looking at the number of pension plans purchased in the years following the financial crisis. The paper is based on data of the study on ‘Life courses and old-age provisions’ (LeA, Lebensverläufe und Altersvorsorge). The data was gathered in 2016 and provides information on the life histories of people living in Germany who were born between 1957 and 1976, as well as on pension entitlements in all three pillars of the German pension system. The analysis concentrates on so-called Riester pension plans, the most dynamic private pension scheme in Germany. We estimate a panel fixed-effects logit model to examine whether the financial crisis had an impact on the participation in Riester pension plans. Results show that instead of a shock effect relating to the crisis years, we see a negative linear effect following the crisis.